Does Renewable Energy Consumption Support Green Growth? - Kuloğlu, Ayhan (Current Studies in Social Sciences VI, 2023)
The rapid growth of production and consumption patterns leads to pollution of natural resources and environmental degradation, with the increase in population worldwide,. This situation requires efficient use of resources to meet the needs of future generations, as well as reducing poverty, inequality, and providing conditions such as health, energy, and clean drinking water. Green growth contributes to sustainable growth by reducing negative externalities from production and increasing positive externalities. In this study, theoretical and empirical studies analyzing whether the use of renewable energy sources supports green growth were examined. As a result, it was observed that the use of renewable energy sources supports green growth through resource efficiency and effectiveness channels.